Przychodze z tym zadaniem tutaj proszę o pomoc!!
Zapisz w najprostszej postaci:

1) 4(3a + 5b) + 3(5a –2) =

2) 2(7p – 3) -5(3p – 1) =

3) -5(2 – 3m) - 2(m + 8) =

4) 2x(3x – 4) + x(5 – 2x) =

5) 3u(2 – 4u) - 5u(u+ 3) =

6) (10t – 6) : (-2) =

7) (3s – 12t + 9) =


Odpowiedź :

Odpowiedź:

1)=12a+20b+15a-6=27a-20b-6

2)=14p-6-15p+5=-p-1

3)=-10+15m-2m-16=-26-13m

4)=6x2-8x+5x-2x2=4x2-3x

5)=6u-12u2-5u2-15u=-9u-17u2

6)=5t+3

7)=3s-12t+9

Odpowiedź:

1) 12a+15b+15a-6= 27a+15b-6

2) 14p-6-15p+5= -p-1

3) -10+15m-2m-16= 13m- 26

4) 6x²-8x+5x-2x²= 4x²-3x

5) 6u-12u²-5u²-15u= -17u²-9u

6) -5t+3

7) 3s-12t+9

Szczegółowe wyjaśnienie: